Digital transformation and human resource management: how are technologies changing the attitude towards human resources? - Uktamova, Dilnoza (MMIT Proceedings, 2025)
This article provides a comprehensive analysis of the impact of digital transformation on human resource management. In the era of globalization and digitalization, the integration of modern information and communication technologies—particularly artificial intelligence, cloud solutions, and automation—is fundamentally reshaping the HR system. Traditional methods are being replaced by new approaches based on data-driven decision-making, performance analytics, virtual learning platforms, and remote work. The article also highlights the evolving roles of HR professionals in a digital environment and emphasizes the importance of key competencies such as digital literacy, flexibility, and strategic thinking. The research findings scientifically substantiate the necessity of utilizing digital solutions for effective human capital management in competitive organizations.